Managing Outsourcing Risks – Challenges and Pitfalls - Crespo de Carvalho, J.; Guimarães, C. (Outsourcing: Strategies, Challenges and Effects on Organizations, 2014)
Book Description: In recent years, due to a more closely connected world, outsourcing has become of growing interest to politicians, firms and workers and thus received a lot of attention in the media and the scientific community. In the public debate, outsourcing is only seen as the acquisition of production parts from abroad. Attended with this fact, many people fear the negative consequences, i.e. job losses. This book discusses managing outsourcing risks; strategic aspects of outsourcing; and outsourcing in industrial energy management.